2013
DOI: 10.17925/use.2013.09.01.37
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Vitamin D Deficiency—Current Concepts on their Impact on Pregnancy

Abstract: Both obesity and vitamin d deficiency are linked to morbidity and ultimately mortality. Vitamin d sufficiency is believed to confer many health benefits; however, with the exception of the classic functions related to bone health these are not yet well understood, especially in relationship to pregnancy and infant health outcomes.1 conversely, insufficiency is associated with adverse health outcomes, which are consequently related to public health concerns that arise from these and these need addressing.2,3 Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In the DALI Vitamin D trial, 25-hydroxyvitamin D baseline levels exceeding 50 nmol/l were reported across all study centres [25••], which was an unexpected finding as previous studies had suggested that a majority of obese pregnant women would have low vitamin D levels [39,40]. Supplementation of 25-hydroxyvitamin D resulted in greater sufficiency in the vitamin D arm, with significant differences in levels compared with placebo at 24-28 (97 vs. 74%) and 35-37 (98 vs. 78%, p < 0.001 both) weeks gestation.…”
Section: Vitamin D and Gdm Riskmentioning
confidence: 94%
“…In the DALI Vitamin D trial, 25-hydroxyvitamin D baseline levels exceeding 50 nmol/l were reported across all study centres [25••], which was an unexpected finding as previous studies had suggested that a majority of obese pregnant women would have low vitamin D levels [39,40]. Supplementation of 25-hydroxyvitamin D resulted in greater sufficiency in the vitamin D arm, with significant differences in levels compared with placebo at 24-28 (97 vs. 74%) and 35-37 (98 vs. 78%, p < 0.001 both) weeks gestation.…”
Section: Vitamin D and Gdm Riskmentioning
confidence: 94%
“…Pregnancy-induced increased body fat mass and hemodilution may explain to some extent the increased vitamin D need of a pregnant woman. Several studies have shown the inverse relationship of body fat mass and vitamin D status (Golzarand, Hollis, Mirmiran, Wagner, & Shab-Bidar, 2018;McAree, 2013). On the other hand, circulating 25(OH)D may decline from the first to the third trimester of pregnancy due to the physiologic hemodilution (Cunningham, 2018).…”
Section: Vitamin D (Maternal and Cord Blood)mentioning
confidence: 99%